All new square foot gardening : the revolutionary way to grow more in less space - Bartholomew, Mel. (Minneapolis, Minn. : Cool Springs Press, 2013)
Square Foot Gardening works; over two million gardeners will agree. That?s how many folks have put Mel Bartholomew?s innovative grid-based method to the test over the years, and always with the same result: more produce in less space with less work.
SFG, new and improved -- Plan your garden -- Building boxes and structures -- Mel's mix, essential for square foot gardening success -- How to plant your all new square foot garden -- Growing and harvesting -- Vertical gardening -- Extending the seasons -- Special gardens & gardeners.
Includes index.
Keywords: Vegetable gardening; Square foot gardening; Vertical gardening; Gardening for children